2499. Burden of Influenza Like Illness (ILI) Among Congregate Military Populations. (26th November 2018) - Coles, Christian; Chen, Wei-Ju; Milzman, Jacqueline Owens; Robinson, Scott; Jones, Carol; Moreno, Nicole; Burgess, Timothy
Abstract: Background: Influenza-like illnesses (ILI) have placed a significant health burden on the United States Armed Forces for decades. Up to 300, 000–400, 000 of new cases of ILI result in clinical encounters in the US military annually. In congregate populations such as trainees, the impact is far greater due to crowding and stressors such as physical stress from training. Clinic-based surveillance may under-estimate the true ILI burden because trainees with ILI may not seek healthcare for fear of missing training, facilitating the spread of respiratory pathogens. To undercover the true ILI burden we estimated the attack rate of ILI in trainees irrespective of whether they sought care. Methods: A prospective cohort study was conducted among US Army recruits in a 9-week basic combat training course at Ft. Benning, GA, in January-March 2017. Symptom diary cards were available to the trainees to record each day whether they had fever/chills/feverish feeling, cough, and/or sore throat, the symptoms of ILI. Attack rate was calculated as number of trainees with ILI divided by number of participants in the study. Results: A total of 78 recruits participated in the study. The participants were male and the mean age was 21 years (SD 4.9). In the first two weeks of training, nine recruits reported to outpatient clinics for their ILI, resulting in an attack rate of 12%. Fifty-five recruits returned symptom diary cards with at least 13 days of records between visit 1 and visit 2. Among them, four trainees visited clinics for ILI while additional 14 trainees reported at least one day of ILI without seeking healthcare. The proportion of patients not seeking care was 78%. The attack rate of self-reported ILI (to health clinics or on symptom cards) was 33% (18/55). The self-reported ILI participants reported a median of 2 days of having ILI (range: 1–7 days). Conclusion: Our data showed that the majority of trainees reporting ILI did not seek healthcare. The attack rate based on clinic attendance largely underestimated the ILI burden. Understanding reasons and obstacles of trainees not seeking care would be crucial in infection control and reduction of ILI transmission among basic training recruits who are at high risk of ILI. Disclosures: All authors: No reported disclosures.